Historia constructiva de la Cartuja de Ara Christi (El Puig, Valencia) 1585-1835 - Barlés Báguena, Elena (Artigrama, 2002)
Fundada en 1585 en el pueblo de El Puig (Valencia), la cartuja de Ara Christi es fruto de una larga historia constructiva que se dilata desde el año 1620, fecha en la que se realizan sus trazas, hasta finales del siglo XVIII. Gracias a la abundante documentación conservada (crónicas históricas y libros de gastos de la obra) se ha podido describir el proceso de edificación de este monasterio, en cuya fábrica trabajaron los maestros de obras y artistas más renombrados de la Valencia de los siglos XVII y XVIII.Founded in the year 1585 in the village of El Puig (Valencia), the charterhouse of Ara Christi is the result of a long construction history that lasted from the year 1620, date in which its planning is carried out, until the end of 18th century. Thanks to the great quantity of preserved documentation (Historical Chronicles and Books of Expenses) we have been able to describe the building of the monastery, in which manufacture worked the most well-known architects and artists of Valencia during the seventeenth and eighteenth centuries.